Diagnostic evaluation in steroid-induced myopathy: case report suggesting clinical utility of quantitative muscle ultrasonography. (2nd October 2018) - Minetto, Marco Alessandro; Caresio, Cristina; D'Angelo, Valentina; Lanfranco, Fabio; Ghizzoni, Lucia; Roatta, Silvestro; Arvat, Emanuela; Kesari, Santosh
ABSTRACT: Purpose : We present a patient with adrenal Cushing's syndrome causing steroid myopathy. The purpose of the case report is to illustrate the clinical usefulness of quantitative muscle ultrasonography for the assessment of glucocorticoid-induced changes in muscle mass (MM) and structure.Methods : Assessments of physical performance, muscle strength, MM (i.e., total body skeletal MM, appendicular skeletal MM, and thickness of lower limb muscles), and muscle structure (i.e., echo intensity of lower limb muscles) were performed in the patient both in the active phase of the disease (preoperatively) and 6 months after surgical intervention (postoperatively).Results : Muscle strength, physical performance, and MM were low both preoperatively and postoperatively. We also found preoperatively an increased echo intensity that normalized postoperatively.Conclusions : Clinical implications of these findings are double-fold. First, although the muscle structure can recover quickly in steroid myopathy patients, the recovery of MM may take months to years. Second, we show that muscle echo intensity can be useful to track the progression of steroid myopathy overtime and may help to indicate early response to therapeutic interventions. Further prospective studies are needed to confirm the value of muscle echo intensity in patients with endogenous or exogenous Cushing's syndrome presenting with steroid myopathy.